Distribution of carbapenemase-producing and colistin resistant Acinetobacter baumannii isolates in Batna hospitals, Algeria - Asma Bouali; Esma Bendjama; Zineb Cherak; Meriem Mennaai; Ahmed Kassah-Laouar; Jean-Marc Rolain; Lotfi Loucif (BMC Infectious Diseases)
Abstract Objective The aim of this study was to investigate the distribution and genetic determinants of carbapenemase production and colistin resistance among Acinetobacter baumannii isolates recovered from three health care facilities in the city of Batna, Algeria. Methods A prospective study was conducted between 2021 and 2022 on 46 Acinetobacter baumannii clinical isolates, which were collected and identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Antibiotic susceptibility testing was performed using the disk diffusion method and colistin minimum inhibitory concentrations (MICs) were determined by broth microdilution method. Carbapenemase and colistin resistance determinants were detected by qPCR. Results The 46 clinical isolates were mainly from the intensive care unit (52.17%) and the burns unit (17.39%). The strains were collected primarily from pus samples (34.78%) and blood samples (17.39%). Eleven strains were classified as colistin-resistant, with MICs ranging from 4 to 128 μg/mL. The bla OXA-24 gene was detected in 63.04% of the isolates, followed by the bla OXA-23 gene (43.47%). Nine strains were positive for both bla OXA-23-like and bla OXA-24-like genes. The bla NDM gene was detected in eight isolates (17.39%), including two which co-expressed a bla OXA-24 gene. In contrast, all strains were negative for the plasmid-mediated colistin resistance mcr-1 to mcr-5 and mcr-8. Conclusion Here, we report a high prevalence of carbapenemases-producing A. baumannii isolates in Batna hospitals. Notably, this study is the first to identify A. baumannii isolates co-producing OXA-24 and NDM carbapenemases and to report the first detection of colistin-resistant A. baumannii co-producing OXA-24 and OXA-23 carbapenemases from a patient in Algeria.